Pengaruh switching cost terhadap word of mouth dengan switching intention sebagai variabel intervening pada pengguna jasa layanan kurir jne di samarinda - Wulandari, Viska (FORUM EKONOMI, 2016)
The aim of this research was to find out the impact of switching cost and switching intention toward word of mouth on courier service JNEs user in Samarinda. The research was conducted on Samarinda by taking a sample of 40 respondents using purposive sampling and questionnaires. The analyze of this research used path analysis. Based on statistical calculation is done with help of software SPSS, it was found hypothesis one is supported because switching cost significantly impacts switching intention, switching intention is significantly impacts word of mouth, and switching cost is not significantly toward word of mouth, so the hypothesis two is supported and hypothesis three is not supported. The implication of this research would be improve connection with user and create the allegiance that can happen obstruct of switching.Keyword: Switching Cost , Switching Intention, Word Of Mouth